The Differences Between Think Pair Share and Stratagem Learning Models in Improving Knowledge of Premature Sex Prevention in Students at SMA Samarinda - Safrudin, Muhammad Bachtiar; Saputri, Della (Universitas Nahdlatul Ulama Surabaya, 2026)
Adolescent growth and development causes physical, cognitive and psychosocial changes, which are followed by sexual maturity, followed by attraction to the opposite sex, thereby triggering the potential for premarital sexual behavior. This problem requires preventive treatment efforts in the form of health education. Health education models that are suitable for upper secondary students are think-pair-share (TPS) and stratagem. This research aims to see the differences in the effectiveness of the think-pair-share and stratagem health education methods on knowledge of premarital sex prevention. This research design uses a quasi-experimental pre- and post-test with a control group design. The population in this study was 120 class X students at SMA 11 Samarinda. The sampling technique used was random sampling with a total of 42 samples each. Adolescent students' prevention knowledge was measured with a questionnaire consisting of 16 items. The research results show a change in knowledge score of 4, given the TPR model education, while the Stratagem model increases by 6. The results of the Mann-Whitney test show a p-value of 0.000 (<0.05), where there is a difference between the TPS and Stratagem models. The stratagem model is suitable for teenagers because of the teenager's character who likes relaxed and fun learning.